Family-based weight stigma and psychological well-being of adolescents: a longitudinal analysis of recent vs. cumulative exposure - Anastasiadou, Dimitra; Tárrega, Salomé; Fornieles-Deu, Albert; Sánchez-Carracedo, David (Frontiers in Psychiatry, 2025)
IntroductionFamily-based weight stigma has been linked to adverse psychological outcomes in adolescents. Research on weight stigma in the Mediterranean area is scarce. This study aims to longitudinally explore the association between family-based weight stigma and adolescents’ psychological well-being, considering recent vs cumulative exposure.MethodsData from the two-year longitudinal WbSad study were drawn from baseline assessments (T1) of a representative sample of 1,016 secondary school adolescents in a large Spanish city. At follow-up (T2), 551 adolescents participated. The mean age at T2 was 15.8 years, with 48.5% girls. Multivariate linear regression models, adjusting for relevant covariates and baseline values, examined the impact of exposure (Never, Only at T1, at T1 and T2, or Only at T2) to family-based weight stigma and to parental comments about weight and dieting on psychological outcomes, measured with the Depression Anxiety Stress Scale-21 (DASS-21) and the Rosenberg Self-Esteem Scale.ResultsFamily-based weight stigma was reported more frequently among girls and was associated with higher psychological distress. Girls exposed to family stigma (at T1 and T2, and Only at T2) reported higher psychological distress, with significant associations across all DASS-21 outcomes for those exposed at T2 only. Maternal comments were linked to greater distress and lower self-esteem in girls and higher stress and total distress in boys at T2 only. Paternal comments at T2 were significantly associated with higher depression and total DASS-21 scores in girls, and higher scores in all DASS-21 outcomes in boys. No significant associations were found between parental encouragement to diet and any psychological outcomes in either gender.DiscussionThis study provides novel insights into how the timing (recency vs. persistent exposure) and source (maternal vs. paternal) of family-based stigma shape adolescent outcomes in a non-Anglo-Saxon sample. Recent family-based weight stigma negatively impacts adolescent psychological well-being, with girls being particularly vulnerable. The absence of an effect from cumulative exposure warrants further exploration. Preventive strategies should educate parents to avoid stigmatizing comments and promote messages that prioritize well-being over weight, particularly before the onset of mid-to-late adolescence. Finally, research is needed to better understand the temporal dynamics of parental weight-related comments and their impact on adolescents.